Dike Propagation During Global Contraction: Making Sense of Conflicting Stress Histories on Mercury - Crane, Kelsey; Bohanon, Allison (Frontiers in Earth Science, 2021)
Thrust fault-related landforms, smooth plains units, and impact craters and basins have all been observed on the surface of Mercury. While tectonic landforms point to a long-lived history of global cooling and contraction, smooth plains units have been inferred to represent more punctuated periods of effusive volcanism. The timings of these processes are inferred through impact cratering records to have overlapped, yet the stress regimes implied by the processes are contradictory. Effusive volcanism on Mercury is believed to have produced flood basalts through dikes, the propagation of which is dependent on being able to open and fill vertical tensile cracks when horizontal stresses are small. On the contrary, thrust faults propagate when at least one horizontal stress is very large relative to the vertical compressive stress. We made sense of conflicting stress regimes through modeling with frictional faulting theory and Earth analogue work. Frictional faulting theory equations predict that the minimum and maximum principal stresses have a predictable relationship when thrust faulting is observed. The Griffith Criterion and Kirsch equations similarly predict a relationship between these stresses when tensile fractures are observed. Together, both sets of equations limit the range of stresses possible when dikes and thrusts are observed and permitted us to calculate deviatoric stresses for regions of Earth and Mercury. Deviatoric stress was applied to test a physical model for dike propagation distance in the horizontally compressive stress regime of the Columbia River Flood Basalt Province, an Earth analogue for Borealis Planitia, the northern smooth plains, of Mercury. By confirming that dike propagation distances from sources observed in the province can be generated with the physical model, we confidently apply the model to confirm that dikes on Mercury can propagate in a horizontally compressive stress regime and calculate the depth to the source for the plains materials. Results imply that dikes could travel from ∼89 km depth to bring material from deep within the lithosphere to the surface, and that Mercury’s lithosphere is mechanically layered, with only the uppermost layer being weak.